Dislocation of the distal radioulnar joint. (October 2018) - Armstrong, Dan; Oni, John
The authors report a case of isolated dislocation of the distal radioulnar joint following sporting injury. We discuss the terminology and suggest that the current description is confusing as the radius dislocates relative to the rigid strut of the ulna rather than the other way round. The mechanism of injury and reduction methods are discussed along with pointers to identify the pathology radiologically.